Quality of Genetically-Improved Acacia auriculiformis For Renewable Short-Rotation Wood-Energy - Rina Laksmi Hendrati; Siti Husna Nurrohmah (Jurnal Manajemen Hutan Tropika, 2018)
To be viable, fast-growing energy plantations must be large in volume, harvested at early age, and maximized calorific value which linked to heartwood proportion. This study examines 38 families in the second generation (F2) progeny trial of Acacia auriculiformis for energy. Heartwood proportion, calorific value and lignin content were assessed at ages 22, 30, 35, and 40 months.  Wood samples from around 300 selected individuals of observed ages from all families were examined. Quality was based on heartwood and sapwood development until reaching the commercial requirement of >33% for lignin content and >4,500 cal g-1 for calorific value.  When required quality has been obtained at particular age, assessment of biomass was carried out from all final individuals in the progeny test. Heartwood proportion varies among families. Heartwood possesses higher values than sapwood in lignin content and calorific value. Individuals with higher heartwood proportion are preferred. Both wood types only reached the required quality for solid wood energy after 3.5 years, however lignin content at much early age are appropriate for wood pellet and briquette. Selection improves heartwood proportion and quality from the first generation (F1) into F2 with an increase of 52% at three years.  Mean annual increments at 3.5 years is 43 m3ha-1yr-1.